2017
DOI: 10.1590/0100-69912017005013
|View full text |Cite
|
Sign up to set email alerts
|

Observation time and spontaneous resolution of primary phimosis in children

Abstract: Objective: to investigate spontaneous resolution rate of a series of patients with physiologic phimosis in relation to observation time and presence of symptoms. Methods: retrospective and longitudinal follow-up study of patients with physiologic phimosis, that did not apply topic treatment. These patients were invited for a new visit for reevaluation, or recent data were obtained by chart analysis. Spontaneous resolution rate was determined and statistically compared to age, presence of symptoms at first medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Similar results were also stated by Kayaba et al on 603 Japanese boys showed that prevalence of completely retractable prepuce gradually increased from 0% of six months baby to 62.9% of child 11 to 15 years old. The study by Laurencao et al observed normal retractions in 45% patients (Lourenção et al, 2017). The study by Tekgul et al found phimosis incidence was 8% at the age of 6-7 years and only 1% in adolescents aged 16-18 years (Tekgul et al, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…Similar results were also stated by Kayaba et al on 603 Japanese boys showed that prevalence of completely retractable prepuce gradually increased from 0% of six months baby to 62.9% of child 11 to 15 years old. The study by Laurencao et al observed normal retractions in 45% patients (Lourenção et al, 2017). The study by Tekgul et al found phimosis incidence was 8% at the age of 6-7 years and only 1% in adolescents aged 16-18 years (Tekgul et al, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…Although circumcision is a minor surgery, patients who receive this surgery tend to hold high expectations for it. Therefore, if there are any post-surgery complications, patients will experience both physical and psychological pain[ 12 ]. Usually, the post-surgery recovery period is long, and the foreskin after surgery is prone to edema.…”
Section: Discussionmentioning
confidence: 99%
“…After approval by the ethics committee of our hospital, the children who underwent circumcision in our outpatient surgery from October 2020 to October 2021 were retrospectively collected, including 112 children aged 6 to 12 years old with phimosis. According to the difference of surgical methods, they were divided into group A (conventional circumcision), group B (ring group), group C (suturing device), with 36 cases in group A, group B was 43 cases, and 33 individuals in group C. Inclusion criteria were as follows: diagnostic criteria: The foreskin tightens over the glans, and the glans cannot be properly exposed even with the aid of external force [2] ; the parents of the children aggressively requested the surgery and signed consent forms for the surgery. Exclusion criteria were as follows: unable to cooperate with local anesthesia; abnormal blood coagulation; with congenital abnormalities of the external genitalia, such as occult penis, hypospadias; serious local penile infection; does not meet the above inclusion criteria.…”
Section: Methodsmentioning
confidence: 99%